Strengthening Filipino Migrants’ Faith through Popular Religiosity - Julia, Norlan (Mission studies, 2016)
The introduction of popular religious practices traditionally held during major liturgical feasts in the Philippines has gathered Filipino migrants in Norwich, United Kingdom, into a dynamic ecclesial community. It has sustained their faith even as they struggle to face the many challenges of living and working abroad and keeping the faith without the comforts and certainties provided by a predominantly Catholic culture at home. They draw courage and consolation from participating in the year-round activities in their Filipino chaplaincies. The author’s pastoral voluntary work in the United Kingdom has been an experience of building an ecclesial community of Filipinos in diaspora, of providing means of support amidst crisis, and of accompanying them in their journey towards a better life and a more meaningful relationship with God.